Update on the urotensinergic system: new trends in receptor localization, activation, and drug design - Chatenet, David; Nguyen, Thi Tuyet Mai; Letourneau, Myriam; Fournier, Alain (Frontiers in Endocrinology, 2013)
The urotensinergic system plays central roles in the physiological regulation of major mammalian organ systems, including the cardiovascular system. As a matter of fact, this system has been linked to numerous pathophysiological states including atherosclerosis, heart failure, hypertension, diabetes as well as psychological and neurological disorders. The delineation of the (patho)physiological roles of the urotensinergic system has been hampered by the absence of potent and selective antagonists for the urotensin-II receptor (UT). Thus, a more precise definition of the molecular functioning of the urotensinergic system, in normal conditions as well as in a pathological state is still critically needed. The recent discovery of nuclear UT within cardiomyocytes has highlighted the cellular complexity of this system and suggested that UT-associated biological responses are not only initiated at the cell surface but may result from the integration of extracellular and intracellular signalling pathways. Thus, such nuclear-localized receptors, regulating distinct signalling pathways, may represent new therapeutic targets. With the recent observation that urotensin-II (UII) and urotensin-II related peptide (URP) exert different biological effects and the postulate that they could also have distinct pathophysiological roles in hypertension, it appears crucial to reassess the recognition process involving UII and URP with UT, and to push forward the development of new analogs of the UT system aimed at discriminating UII- and URP-mediated biological activities. The recent development of such compounds, i.e. urocontrin A and rUII(1-7), is certainly useful to decipher the specific roles of UII and URP in vitro and in vivo. Altogether, these studies, which provide important information regarding the pharmacology of the urotensinergic system and the conformational requirements for binding and activation, will ultimately lead to the development of potent and selective drugs.